Numerical Investigation of the Hydrodynamic Characteristics of 3-Fin Surfboard Configurations - Sam Crameri; Paul K. Collins; Saleh Gharaie (Applied Sciences, 2022)
Surfing is a popular sport, with the associated market forecast to reach 2.6 billion US dollars by 2027. In the published literature, there is a range of investigations into the performance of surfboard fins. Some studies model a single fin or review the performance of different fin layouts and surface designs. However, the effects of individual fin design features on flow dynamics are not well understood. This study provides numerical analysis into the thruster fin aspects (rake, depth, and base length) and resultant key performance indicators (i) lift and drag coefficients, and (ii) turbulent kinetic energy. The models were simulated in Ansys Fluent R19.1, solving steady Reynolds-averaged Navier–Stokes equations using the SST k−ω turbulence model at a velocity of 7 m/s. The results indicate the performance of fins varies more post-stall. The variations in rake showed the biggest impact on the turbulence intensity at an angle ≥20°. The variations in base length exhibited coefficient trends with greater lift at small angles but significant lift losses at high angles of attack. The variations in depth affected the forces on the fins rather than the performance indicators. Based on these simulations, a proposed fin set was developed that presented the lowest lift losses after the stall point.